1997
DOI: 10.1073/pnas.94.8.3893
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation determines hot spots of DNA damage in the human  P 53 gene

Abstract: In the P53 tumor suppressor gene, a remarkably large number of somatic mutations are found at methylated CpG dinucleotides. We have previously mapped the distribution of (؎) anti-7␤,8␣-dihydroxy-9␣,10␣-epoxy-7,8,9,10-tetrahydrobenzo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
232
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(250 citation statements)
references
References 53 publications
15
232
0
1
Order By: Relevance
“…17,20,21,51,52 While this view has been challenged, 53,54 there is accumulating in vitro evidence that the methylation of cytosine in CpG dinucleotide steps indeed enhances the reactivity of B[a]PDE with the guanine residue in meCpG sequence contexts. 23,24,26,55,56 This effect is most likely associated with the hydrophobicity of the methyl group that enhances both the non-covalent intercalative binding of B[a]PDE to double-stranded poly(dG-me dC)·poly(dG-me dC) and the subsequent yield of covalent [BP]G adduct formation 55,57 as observed in p53 oligonucleotide sequence 17,20,21,23,24,26 and other sequence contexts. 25 …”
Section: Discussionmentioning
confidence: 99%
“…17,20,21,51,52 While this view has been challenged, 53,54 there is accumulating in vitro evidence that the methylation of cytosine in CpG dinucleotide steps indeed enhances the reactivity of B[a]PDE with the guanine residue in meCpG sequence contexts. 23,24,26,55,56 This effect is most likely associated with the hydrophobicity of the methyl group that enhances both the non-covalent intercalative binding of B[a]PDE to double-stranded poly(dG-me dC)·poly(dG-me dC) and the subsequent yield of covalent [BP]G adduct formation 55,57 as observed in p53 oligonucleotide sequence 17,20,21,23,24,26 and other sequence contexts. 25 …”
Section: Discussionmentioning
confidence: 99%
“…A similar predilection for C-to-T transition mutations at CpG dinucleotides within arginine codons has been noted in p53 and retinoblastoma gene mutations (18,19) and has been ascribed to methylation of cytosine by endogenous methyltransferases with subsequent deamination to thymine. Whereas this type of mutation has traditionally been thought to be unrelated to exogenous factors, some studies have suggested that the 5-methylcytosine may also serve as a target for carcinogens (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…All the mutational hot spots (codon 175, 245, 248, 273, 282) contain CpG dinucleotide and the cytosine of this dinucleotide is often methylated in mammalian cells (Tornaletti and Pfeifer, 1995b;Soussi and Beroud, 2003). Both exogenous carcinogens (for example UV) and endogenous mutagens (such as altered cell metabolism) can target methylated CpG dinucleotide, leading to a high rate of transitions in p53 (Tornaletti and Pfeifer, 1995a;Denissenko et al, 1997). Distribution of mutations in p53 shows various mutational hot spots (figure 4) and the spectra of hot-spots differ among various tumor types.…”
Section: Discussionmentioning
confidence: 99%